2015
DOI: 10.1155/2015/530541
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Mineral Element Content in a Functional Food Maca (Lepidium meyeniiWalp.) from Asia and South America

Abstract: Contents of eight mineral elements in maca (Lepidium meyenii Walp.) from China and Peru were determined by inductively coupled plasma optical emission spectroscopy. Cu contents in maca samples from China (2.5–31 mg kg−1 dry weight, dw) were higher than the samples from Peru (<2.1 mg kg−1 dw). Na in two samples from China was found to be significantly of high content (2400 and 2600 mg kg−1 dw). The contents (mg kg−1 dw) of B, Co, Cr, Li, Ni, and Zn were, respectively, 8.1–21, <0.023, <1.1~3.5, 0.020–0.17, 0.085… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Other studies have shown that the cultivation area can significantly affect the nutritional and metabolite content of maca. For example, yellow maca samples grown in China had a higher mineral and protein content than yellow maca grown in Peru (Zhang et al, 2015, Chen et al, 2017. Additionally, most scientific studies investigated the properties of Peruvian maca but not Chinese maca (see appendix 2).…”
Section: Cultivation Practices and Area Of Cultivationmentioning
confidence: 99%
“…Other studies have shown that the cultivation area can significantly affect the nutritional and metabolite content of maca. For example, yellow maca samples grown in China had a higher mineral and protein content than yellow maca grown in Peru (Zhang et al, 2015, Chen et al, 2017. Additionally, most scientific studies investigated the properties of Peruvian maca but not Chinese maca (see appendix 2).…”
Section: Cultivation Practices and Area Of Cultivationmentioning
confidence: 99%
“…Maca had been extensively investigated because of its applications in sexual and fertility enhancement (Gonzales and others ; Massoma Lembè and others ), hormonal regulation (Gonzales and others ), antifatigue properties (Choi and others ), and impaired memory alleviation (Rubio and others ), which have been demonstrated in animal and human trials. Previous studies focused on macamides and macaenes (Esparza and others ; Zhang and others ), alkaloids (Zhao and others ), and polyphenols (Bai and others ), whose contents are much less than those of maca polysaccharides (MPs). Although the isolation, monosaccharide composition, immunomodulatory effects (Zhang and others ), and antioxidant activities in vitro of MP had been described (Zha and others ; Wang and others ), the detailed chemical structure and antifatigue effect in vivo of MP have seldom to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…Although many attempts have been developed to cultivate this plant in other settings including the use of the same seeds from the Peruvian Central Andes, the hypocotyl size does not resemble the native Peruvian one. These approaches have been described for United States, Germany, Czech Republic (Melnikovova, Havlik, Fernandez Cusimamani, & Milella, ) and more recently from China (Zhang et al., ).…”
Section: Introductionmentioning
confidence: 99%